Implikasi variabel fundamental keuangan terhadap manajemen laba: mampukah Corporate Social Responsibility sebagai variabel intervening - Sriyono Sriyono; Anggraeni Dwi Fitria (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
Many ways will be done by the company in order to attract investors, one of which is by doing earning management. Previous studies have researched earning management, but it is still limited to discussing the use of corporate social responsibility (CSR) as an intervening variable. This research includes new research because using corporate social responsibility (CSR) intervening variables, the existence of intervening variables is expected to be able to test the mediating role of financial fundamental variables to strengthen this earning management. This study aims to find out the role of corporate social responsibility as a mediator of financial fundamental variables (capital adequacy ratio, firm size, and tax planning) on earning management. This research is quantitative research using data panel regression analysis techniques and path analysis using the Eviews Program. The population used in this study is all conventional banks listed on the Indonesia Stock Exchange, sampling techniques used are purposive sampling. The results found a relationship between CAR, firm size, tax planning, CSR with earning management and corporate social responsibility plays a role as mediation. The conclusion obtained in this study is corporate social responsibility is able to be mediating the relationship between CAR and earning management and corporate social responsibility is able to mediate the relationship between firm size to earning management.